Small and Medium Enterprises and Social Media Usage: A Fashion Industry Perspective - Tumsifu, Elly; Dev, Jani; Gekombe, Caleb (University of Dar es Salaam Library Journal, 2021)
This article examines how social identity, perceived usefulness and perceived ease of use of social media influence the use of social media in Small and Medium Enterprises dealing with fashion, in Kenya. The study was informed by the Social Identity Theory, Technology Acceptance Model and Theory of Planned Behaviour. A total of 150 managers who owned small and medium Enterprises dealing with fashion, from Nairobi and Kiambu counties, were surveyed using a structured questionnaire. Collected data was analysed mainly through regression analysis. Findings show that perceived ease of use and perceived usefulness towards social media usage bear significant influence on usage of social media whereas social identity was not significant and hence no influence on social media use. The fashion industry in Kenya was found to be dominated by females with most of them using Facebook compared to other social media platforms. These findings however suggest not only that social media use is limited to communication, but it is relevant for knowledge sharing, content generation, information storage and retrieval among current users and future patrons.